A cohort study of duplicate faecal immunochemical testing in patients at risk of colorectal cancer from North-West England. Issue 4 (13th April 2022) - Hunt, Natalie; Rao, Christopher; Logan, Robert; Chandrabalan, Vishnu; Oakey, Jane; Ainsworth, Claire; Smith, Neil; Banerjee, Saswata; Myers, Martin
Abstract : Objectives: We sought to investigate if duplicate faecal immunochemical testing (FIT) sampling improves the negative and positive predictive value of patients thought to be at risk of colorectal cancer (CRC). Specifically, we aimed to investigate whether the proportion of FIT-negative CRC missed by a single FIT test in symptomatic patients could be reduced by duplicate FIT testing. Design: A retrospective service evaluation cohort study of the diagnostic accuracy of duplicate FIT testing. Setting: Patients referred from primary care with suspected CRC to four secondary care trusts in North-West England. Participants: 28 622 patients over 18-years-old with lower gastrointestinal symptoms suggestive of CRC who completed two FIT samples. Primary and secondary outcome measures: The performance of duplicate FIT for detecting CRC at a threshold of 10 µgHb/g. Results: The sensitivity if either test was >10 µgHb/g was 0.978 (0.955–0.989), specificity was 0.662 (0.657–0.668), positive predictive value 0.031 (0.028–0.035) and negative predictive value 1.00 (0.999–1.00). Despite two-thirds of patients (18952) being negative following two tests, at this threshold only seven CRC were missed over a 26-month period. All seven patients had other high-risk features which should have prompted investigation. Conclusions: This study suggests that in routine NHS practice, a duplicate FIT sample strategy together with clinical evaluation for evidence of anaemia and weight loss is superior to a single FIT sample alone and would allow symptomatic patients to be managed in primary care without the need for urgent referral to secondary care for urgent colonic imaging.